2015
DOI: 10.1159/000441982
|View full text |Cite
|
Sign up to set email alerts
|

Intradialytic Blood Pressure Abnormalities: The Highs, The Lows and All That Lies Between

Abstract: Background: Frequent blood pressure (BP) measurements are necessary to ensure patient safety during hemodialysis treatments. Intradialytic BPs are not optimal tools for hypertension diagnosis and cardiovascular risk stratification, but they do have critical clinical and prognostic significance. We present evidence associating intradialytic BP phenomena including fall, rise and variability with adverse clinical outcomes and review related pathophysiologic mechanisms and potential management strategies. Summary:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
75
2
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(82 citation statements)
references
References 72 publications
3
75
2
2
Order By: Relevance
“…Currently our interventions to IDH are reactive, relying upon rapid nursing assessment and intervention. Typical reactive interventions include: repositioning patient to optimize hemoperfusion of vital organs (supine or Trendelenburg position); cessation of ultrafiltration; fluid resuscitation via isotonic saline, hypertonic saline or glucose; and in some centers albumin and cessation of dialysis [13,21]. Although these interventions are necessary and beneficial, they may not prevent the adverse consequences of IDH events.…”
Section: Association Of Proportion Of Intradialytic Hypotensive Eventmentioning
confidence: 99%
“…Currently our interventions to IDH are reactive, relying upon rapid nursing assessment and intervention. Typical reactive interventions include: repositioning patient to optimize hemoperfusion of vital organs (supine or Trendelenburg position); cessation of ultrafiltration; fluid resuscitation via isotonic saline, hypertonic saline or glucose; and in some centers albumin and cessation of dialysis [13,21]. Although these interventions are necessary and beneficial, they may not prevent the adverse consequences of IDH events.…”
Section: Association Of Proportion Of Intradialytic Hypotensive Eventmentioning
confidence: 99%
“…Moreover, higher slopes of RBV decline were associated with an increase in arterial oxygenation, suggesting a beneficial effect on pulmonary oxygen exchange due to fluid removal [10]. Therefore, it might be suggested that higher ultrafiltration rates may be associated with increased mortality because of impaired tissue perfusion, and because of the accompanied patient characteristics, a low decline in blood volume or a rise in SBP may be associated with adverse outcomes because of concomitant fluid overload in these patients [22, 23]. In a recent study, we noticed that the prognostic value of changes in SBP was related to the pre-dialytic blood pressure.…”
Section: A Fall In Blood Pressure During Dialysis Is Not Always Detrimentioning
confidence: 99%
“…While prevention of interdialytic weight gain by sodium restriction is a cornerstone of treatment [41], the dilemma between too rapid fluid removal and persistent fluid overload may in some cases be solved only by increasing dialysis time and/or frequency [42]. As preventive methods have been discussed in detail both in older and more recent literature [8, 23], we will focus here on recently published trials. Antlanger et al [43] randomized fluid overloaded patients, defined as an overhydration/extracellular water ratio above 15%, to a reduction in dry weight using conventional strategies, to ultrafiltration-dialysate conductivity controlled feedback modelling and to ultrafiltration-temperature controlled feedback.…”
Section: Preventionmentioning
confidence: 99%
“…2,8,9 Observational data suggest that intradialytic hypertension may represent a modifiable risk factor among individuals receiving maintenance hemodialysis. A predialysis to postdialysis systolic BP rise (vs. decline) has been associated with increased long-term morbidity and mortality.…”
mentioning
confidence: 99%